Art curation and critique in the age of digital humanities. Issue 2 (4th May 2019) - Cruz, Maria Teresa
ABSTRACT: Research and selection of information, as well as its display and analysis, have become central to our daily lives. They are interestingly close to the cultural techniques that preside to the production of knowledge and to art-related practices, such as curating, exhibiting and critique, which seems to bring testimony to the triumph of the so-called 'knowledge society' and 'creative economy'. But, while both scientific knowledge and cultural industry are rapidly relying on algorithms, automated analysis and data visualisation to deal with the exponential growth of data, cultural institutions and humanities are still struggling to decide in what terms are they going to enter the digital age, although they are already being transformed through the infrastructure of digital archives and digital media. This proposal will reflect upon the meaning of activities such as curating, displaying and critique, that have shaped the worlds of art and culture over the last century and upon their redefinition by the mathematics and geometry that are developping the new information geographies of the cultural economy.